Analisis Pengaruh Kendala Pengadaan Tanah Terhadap Pembangunan Kawasan Ekonomi Khusus (Kek) Maloy Kecamatan Kaliorang Kabupaten Kutai Timur Ditinjau Dari Undang-Undang Nomor 2 Tahun 2012 Tentang Pengadaan Tanah Bagi Pembangunan Untuk Kepentingan Umum - Pasaribu, Parlindungan; Fatwa, Nasrul Abdal (Law Department, University of Widya Gama Mahakam Samarinda, 2021)
This study aims to find out the constraints of land acquisition of Maloy Special Economic Zone (KEK) conducted by the East Kutai Regency Government in the review of Law No. 2 of 2012 on Land Procurement for Development for the Public Interest. This research is normative legal research sourced from Secondary legal materials and primary legal materials. The results of this study showed that the constraints of land procurement in the Special Economic Zone (KEK) Maloy in its implementation occurred negligence caused by several factors. So it is recommended that the Government of East Kutai Regency in conducting land procurement activities in the Maloy Special Economic Zone (KEK) should follow the mechanism of land procurement properly so that all the processes are not harmed.